Ab initio electronic structure study of a model water splitting dimer complex. Issue 48 (23rd November 2015) - Fernando, Amendra; Aikens, Christine M.
Abstract : The electronic structure of a model Mn dimer is examined during the water splitting mechanism using multiconfigurational methods. Abstract : A model manganese dimer electrocatalyst bridged by μ-OH ligands is used to investigate changes in spin states that may occur during water oxidation. We have employed restricted open-shell Hartree–Fock (ROHF), second-order Møller–Plesset perturbation theory (MP2), complete active space self-consistent field (CASSCF), and multireference second-order Møller–Plesset perturbation theory (MRMP2) calculations to investigate this system. Multiconfigurational methods like CASSCF and MRMP2 are appropriate methods to study these systems with antiferromagnetically-coupled electrons. Orbital occupations and distributions have been closely analyzed to understand the electronic details and contributions to the water splitting from manganese and oxygen atoms. The presence of Mn(iv )O˙ radical moieties has been observed in this catalytic pathway. Multiple nearly degenerate excited states were found close to the ground state in all structures. This suggests competing potential energy landscapes near the ground state may influence the reactivity of manganese complexes such as the dimers studied in this work.